Sistem Informasi Absensi PPNPN (Pegawai Pemerintah Non Pegawai Negeri) pada Pengadilan Negeri Takengon Berbasis Web - Wati, Rayu; Rejeki, Desi; Syahputra, Hendri (Universitas Gajah Putih, 2026)
Attendance systems play an important role in human resource management because they are directly related to employee discipline, performance, and accountability. The District Court of Takengon currently applies a manual attendance system, which has several limitations such as a high risk of recording errors, potential data manipulation, and time-consuming attendance recap processes. This study aims to design and implement a web-based attendance information system for Government Non-Civil Servant Employees (PPNPN) in order to improve the efficiency and accuracy of attendance data management. The research method used is a descriptive study with a system development approach employing the Waterfall model, which consists of requirement analysis, system design, implementation, testing, and maintenance stages. The system was developed using the PHP programming language with a MySQL database and operated through a local XAMPP server. The results show that the proposed web-based attendance information system is able to record employee attendance digitally, generate attendance reports automatically, and enhance transparency and efficiency in personnel administration processes. Therefore, the system is expected to support more effective human resource management at the District Court of Takengon.